Introducing visual participatory methods to develop local knowledge on HIV in rural South Africa. Issue 3 (28th September 2017) - Brooks, Chloe; D'Ambruoso, Lucia; Kazimierczak, Karolina; Ngobeni, Sizzy; Twine, Rhian; Tollman, Stephen; Kahn, Kathleen; Byass, Peter
Abstract : Introduction: South Africa is a country faced with complex health and social inequalities, in which HIV/AIDS has had devastating impacts. The study aimed to gain insights into the perspectives of rural communities on HIV-related mortality. Methods: A participatory action research (PAR) process, inclusive of a visual participatory method (Photovoice), was initiated to elicit and organise local knowledge and to identify priorities for action in a rural subdistrict underpinned by the Agincourt Health and Socio-Demographic Surveillance System (HDSS). We convened three village-based discussion groups, presented HDSS data on HIV-related mortality, elicited subjective perspectives on HIV/AIDS, systematised these into collective accounts and identified priorities for action. Framework analysis was performed on narrative and visual data, and practice theory was used to interpret the findings. Findings: A range of social and health systems factors were identified as causes and contributors of HIV mortality. These included alcohol use/abuse, gender inequalities, stigma around disclosure of HIV status, problems with informal care, poor sanitation, harmful traditional practices, delays in treatment, problems with medications and problematic staff–patient relationships. To address these issues, developing youth facilities in communities, improving employment opportunities, timely treatment and extending community outreach for health education and health promotion were identified. Discussion: Addressing social practices of blame, stigma and mistrust around HIV-related mortality may be a useful focus for policy and planning. Research that engages communities and authorities to coproduce evidence can capture these practices, improve communication and build trust. Conclusion: Actions to reduce HIV should go beyond individual agency and structural forces to focus on how social practices embody these elements. Initiating PAR inclusive of visual methods can build shared understandings of disease burdens in social and health systems contexts. This can develop shared accountability and improve staff–patient relationships, which, over time, may address the issues identified, here related to stigma and blame.